Government funding incentives and felony charge rates - Cotti, Chad (Journal of crime and justice, 2022)
Using data from the State of Wisconsin’s Consolidated Court Automation Programs (CCAP), we find evidence that Wisconsin’s District Attorneys decisions on how to file criminal complaints (charges) changed meaningfully in 2001 and 2009. These changes align with changes in the State’s funding process for District Attorneys (DAs). Specifically, after the introduction and alterations of a formula-based funding process, which is determined by charges filed, we find an increase in the number of felony charges. Further, we only observe this increase where prosecutorial discretion exists. Finally, relative to misdemeanors, we find a discontinuous increase in charges that is consistent with the formula. In summary, we find evidence consistent with a relationship between DA funding policies and DA behavior.